New Testament textual criticis m the application of thoroughgoing principles : essays on manuscripts and textual variation - Elliott, J. K. (Novum Testamentum, Supplements, 2010)
J.K. Elliott has been identified as one of the Main exponents of so-called thoroughgoing textual criticism. In this collection of fifty seven of his essays from the past forty years are articles on methodology as well as on praxis (with a selection of important textual variants, including some of especial interest for exegesis). Also included are several essays on textual criticism which emphasise its relevance for the discussion of the synoptic problem and there are also a number of assessments of printed editions of the Greek New Testament. A bibliography of Elliott's writings is appended. Those interested in the New Testament text and in Greek manuscripts as well as scholars working on the history of exegesis or the Greek language which thoroughgoing criticism encourages will find this collection of value. The selection will enable readers to have an overview of Elliott's contribution to the discipline.